Physiological Response to Heat Stress in Immune Phenotyped Canadian Holstein Dairy Cattle in Free-Stall and Tie-Stall Management Systems - Cartwright, Shannon; Schmied, J.; Livernois, A.; Mallard, B. A. (Frontiers in Animal Science, 2022)
The climate in northern latitude countries, such as Canada, are changing twice as fast as lower latitude countries. This has resulted in an increased frequency of hot days and longer more frequent heat waves. Canadian dairy cattle are therefore at increased risk of heat stress, especially those in management systems without the infrastructure to properly cool animals. Cattle experiencing heat stress undergo numerous physiological changes. Previous research has shown dairy cattle classified as high immune responders have lower incidence of disease. Therefore, the objective of this study was to evaluate the variation in respiration rate, rectal temperature, and rumination activity in immune phenotyped dairy cattle during a natural heat stress challenge. Additionally, the relationship between physiological response and temperature humidity index was compared between free-stall and tie-stall management systems. A total of 27 immune phenotyped (9 high, 9 average and 9 low) lactating dairy cattle were housed in a free-stall during the summer months for a duration of 27 days. Concurrently, 2 groups of 6 (3 high and 3 low) immune phenotyped lactating dairy cattle were housed in a tie-stall for a duration of 12 days. Rumination was measured for the duration of the study for all cattle using SCR Heatime rumination collars. Respiration was measured using EMKA respiration bands for cattle housed in the tie-stalls, and manually (once in the morning (am) and once in the afternoon (pm)) for cattle in free-stall management. Rectal temperature was measured using a digital thermometer twice daily (am and pm) in both free-stall and tie-stall management systems. The temperature humidity index was recorded every 15 minutes in both management systems for the duration of the study. The results showed that high responders had significantly lower respiration rates compared to low responders when the temperature humidity index was high in both free-stall and tie-stall management systems, but there was no difference in rectal temperature, or rumination activity between phenotypes. Temperature humidity index values in the free-stall were significantly lower than the tie-stall. These findings increase the evidence that high immune responders are more likely to be tolerant to heat stress than low immune responders.